Feeding finishing heavy pigs with corn silages: effects on backfat fatty acid composition and ham weight losses during seasoning. Issue 4 (2nd October 2017) - Capraro, Diego; Buccioni, Arianna; Piasentier, Edi; Spanghero, Mauro
Abstract: The effect of diets containing corn silages (whole ear or high cut whole plant corn silages, WECS and HCCS, respectively) on fatty acid composition of back fat and the weight loss of thighs during the seasoning process were examined in Italian heavy pigs (from 90 to 160 kg of live weight). Two trials were conducted in the same farm, following an identical experimental protocol. In both trials, a control diet, based on dry corn, barley, wheat, extracted soybean meal, wheat bran and supplement (47, 23, 10, 9, 8 and 3% dry matter (DM), respectively) was compared with a diet containing 30% DM of WECS (trial 1) or 20% DM of HCCS (trial 2) in substitution of bran and part of the corn. The initial fresh weight of thighs was very homogeneous between the two trials and only at the end of seasoning the hams from pigs fed the corn silage diets were slightly lighter (of about 0.5 kg, p  < .05). The dietary inclusion of corn silages determined a significant increase of the saturated fraction of the back fat (from 40.6 to 41.9%, p  < .05), mainly due to the increase of the C 18:0 fatty acid (from 14.3 to 15.2%, p  < .05). Overall, the calculated iodine value was favourable for the fat of pigs fed silages (62.63 vs. 64.24, p  = .05). In conclusion, feeding corn silages to heavy pigs has limited impact on seasoning ham losses and can slightly improve backfat quality, in terms of fatty acid composition.